Geochemistry of trace metals and organic matter in equatorial estuaries of Northeastern Brazil - Santos, Thays Thayanne Luz (2022)
The Parnaíba River Delta (PRD) is a coastal Environmental Protection Area (APA) located in the Equatorial Zone of Northeast Brazil (EZNB), composed of estuaries, islands, bays and dunes. The APA is located in the third-largest mangrove forest in the world and can provide a large amount of organic matter (OM) to the environment. The review of the literature provided the trace metal fate in the EZNB’s estuaries that showed enrichment of trace metals in PRD sediments, originating from natural processes and from anthropogenic sources, similar to heavily urbanized coastal environments of the region, and the OM is one of the three main geochemical carrier of metals observed in the region. Therefore, the present work hypothesizes that trace metals from natural and non-natural sources can be controlled by dissolved organic matter (DOM) from the mangrove forest, which act as a geochemical carrier that regulates the partition, mobility and possible toxicity to the biota under the geochemical and hydrodynamic conditions of the equatorial estuary of the PRD. Sampling campaign was performed in December 2019 to collect subsurface water to obtain the dissolved and particulate fractions. The fractions were collected at thirteen stations along an extension of approximately 76 km from the main channel of the Parnaíba River to the Tutóia Bay. In parallel, water samples were also taken at six stations along a salinity gradient (0-36) for the ultrafiltration procedure, totaling 42 subsamples. In the dissolved fractions, trace metals, dissolved organic carbon (DOC), UV- Visible absorption spectrophotometry, composition of OM by fluorescence, and complexation capacity of OM with copper were determined. Suspended particulate matter (SPM) and the trace metal content in the SPM were determined in the particulate fraction. All analyzes were performed in duplicates. The results of environmental quality index indicated anomalies for the Zn in the particulate fraction suggesting possible anthropogenic enrichment through domestic effluents and agricultural activities. The trace metals in the particulate fraction showed desorption increase to the dissolved fraction with salinity rise, as observed mainly for Ba and Zn. This behavior was evident with the distribution coefficient that indicated potential mobility for Ba, Zn and Cu. Fluorescence confirmed the contribution of mangroves in the composition of DOM. The DOM showed a composition of humic substances of terrestrial origin (degradation of mangrove plant material) and of primary productivity (peaks A+C), as well as of marine origin (peak M) of microbial oxidation and phytoplankton degradation. Autochthonous DOM is more labile with lower molecular weight and low aromaticity, while allochthonous DOM has structures with high molecular weight, aromaticity and they are more refractory. The complexation capacity showed a strong interaction of DOM with Cu in the stations of the Mangrove Channel, suggesting a tendency of lower availability of metal in the water, and the low values found in the waters of the Main River and the Bay area. Fluorescence decomposition of ultrafiltration subsamples identified protein-like components, in addition to the humic substances identified previously. Therefore, the present study characterized the importance of MOD of high molecular weight, aromatic and refractory mangroves in the control trace metal partitioning in the equatorial estuarine system, as this case study of DRP.